VIDEO PROJECT ASSIGNMENT IN ENGLISH FOR SPECIFIC PURPOSES (ESP): STUDENTS’ PERCEPTION - Asep Suhana; Ricky Ekaristy Purwadi (ELTIN Journal, 2023)
The purpose of this study was to investigate students' perception on the use of video projects as English-speaking assignments in English for Specific Purpose (ESP) at STIEB Perdana Mandiri. This research implemented the case study of qualitative research methods. The third semester students of STIEB Perdana Mandiri's Business Management study program were the subjects of research. The total number of students is 122, and the researchers decided 50 of them as the subjects for this study using Purposive Sampling. The survey method in this study was descriptive quantitative. Data was gathered using questionnaires were distributed via Online questionnaires. The interview includes 30 questions about the students' video- creating process and their perceptions of video projects for English speaking assignments in English for Specific Purposes (ESP). According to the results of the questionnaires, most of the respondents had positive opinion of video project assignments in English for Specific Purposes (ESP). In conclusion, the students are interested in learning English in English for Specific Purposes, and the video project can help them become more confident in speaking. Smartphones can also be useful in learning English. Keywords: Assignment, ESP, Students’ Perception, Video Project